Do Non-tariff Barriers to Trade Save American Jobs and Wages? - Marco Leonardi; Elena Meschi (Institute of Labor Economics (IZA), 2021)
Before the recent rebound due to the US–China trade war, tariffs on international trade were being progressively reduced over the last decades and advanced countries increasingly relied on non-tariff measures (NTMs) to protect their industries from foreign competition. In this paper, we exploit a novel database on NTMs to test their role in shaping the labour market effects of exposure to Chinese import competition over the 2000–2015 period. We relate changes in manufacturing employment to the share of employed workers protected by NTMs across US local labour markets and we instrument NTMs using the industry share of employment in swing states during presidential elections. Our results indicate that NTMs mitigate the negative employment effect of exposure to Chinese imports and have a positive effect on manufacturing wages (especially for the unskilled).
Keywords: E24; J23; J31; 330; import competition; non-tariff barriers; labour market; Chinese imports